2017
DOI: 10.1606/1044-3894.2017.98.13
|View full text |Cite
|
Sign up to set email alerts
|

African American Fathers: Disproportionate Incarceration and the Meaning of Involvement

Abstract: Impoverished and African American fathers are often criticized by policy makers for lack of involvement in their children's lives. These criticisms are limited to defining responsible fatherhood as providing economic support while ignoring other forms of nurturing. Recent studies provide a broader perspective on how impoverished and African American fathers nurture their children. This article analyzes data from five studies carried out in Syracuse, New York, between 1996 and 2011. The studies support the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…While honoring the words of the mothers, we do not want to leave the impression that we have told a complete story. In analysis with babies’ fathers conducted by our team in another community (Keefe et al, 2017), we found that fathers describe trying to get close to their children and at times not being able to do so because of their babies’ mothers’ anger, as well as because of unemployment and disproportionate incarceration, which make maintaining an active role in the children’s lives difficult.…”
Section: Resultsmentioning
confidence: 99%
“…While honoring the words of the mothers, we do not want to leave the impression that we have told a complete story. In analysis with babies’ fathers conducted by our team in another community (Keefe et al, 2017), we found that fathers describe trying to get close to their children and at times not being able to do so because of their babies’ mothers’ anger, as well as because of unemployment and disproportionate incarceration, which make maintaining an active role in the children’s lives difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The African American rate was therefore 99 times the white rate (see also Lane et al 2017a). Keefe et al (2017) found that the disproportionate incarceration of men of color was one of the key reasons for female-headed households in that group. While racial inequality in incarceration affects women, the vast majority of individuals sentenced are men, many of whom are the fathers of the youth and young adults experiencing the murders of friends and family members.…”
Section: Inequality and Homicide In Syracusementioning
confidence: 99%
“…We formalized this aspect of our university-community partnership as the Syracuse Neighborhood Violence Research Collaboration. Together we have developed interventions, written grants, and published peer-reviewed articles (Bergen-Cico et al 2015;Jennings-Bey et al 2015;Keefe et al 2017;Lane et al 2017a;Larsen et al 2017). The impetus for this article on unaddressed grief, memory, and future retaliation emerged from this earlier work.…”
mentioning
confidence: 99%
“…These challenges often include poverty, incarceration, unemployment, substance abuse, lack of parenting skills, trauma, depression, or the competing demands of multiple children with multiple mothers (Edin & Nelson, 2013; Roy & Dyson, 2010). In addition, men of color are further impacted by current forms of discrimination and policies that create or reinforce structural and institutional barriers such as poverty, persistent racial inequality, and disproportionate incarceration (Bhenke & Allen, 2007; Keefe et al, 2017; Mills, 2010; Waller & Swisher, 2006). The stressors of surviving any one of these challenges can lead to depression, a reduction in behavioral and emotional engagement, relationship fragility with the mothers, and ultimately reduced father involvement in the lives of their children (Coakley, Kelley, & Bartlett, 2014; Roy & Dyson, 2010).…”
Section: Locating Father Involvementmentioning
confidence: 99%
“…For example, in 2015, OFA awarded 5-year RF grants to 39 organizations, Healthy Marriage grants to 46 organizations, and additional awards to programs that serve incarcerated fathers and fathers reentering society (Israel, Behrmann, & Wulfsohn, 2017). Incarcerated fathers (disproportionately represented by African Americans), and those reentering their communities, confront significant barriers to responsible fatherhood, including insufficient preparation for reentry that inhibits the capacity of a father to provide for his children (Keefe et al, 2017; Perry & Bright, 2012). One promising reentry program (located in Cincinnati, Ohio called the Cognitive Behavioral Intervention for Justice Involved Individuals Seeking Employment) combines traditional job-readiness services and cognitive behavioral skill-building to aid men with their efforts to join the marketplace (Israel et al, 2017).…”
Section: Implications For Practicementioning
confidence: 99%